Theoretical and Practical Implications of Evidence in Religion Court - Muhiddin Muhiddin (UIN Sunan Gunung Djati Bandung, 2020)
In the civil procedural law, the certainty of the truth of the events proposed at the trial depends very much on the evidence carried out by the parties concerned. As a consequence, the truth is said to exist or be reached if there is a match between the judge's conclusion (the result of the process) and the events that have taken place. Whereas if the opposite happens, it means that the truth is not reached. Research conducted by the author is research based on document research (Library Research), meaning that the data that are used as a reference in this study are facts in the field that have been documented in the Court's decision. The results of this study indicate that the contribution of evidence in court is very necessary, because one of the duties of the judge is to investigate whether there is a legal relationship on which the lawsuit really exists or not. The existence of this legal relationship must be proven by the parties in court.